2011
DOI: 10.4103/2230-8229.90009
|View full text |Cite
|
Sign up to set email alerts
|

Inpatients′ care experience and satisfaction study

Abstract: Objective and Background:Measures to promote patient satisfaction are important components of the assessment of outcome and strategies for the delivery of health care. In this article, we assess satisfaction among inpatients and the impact of demographics on satisfaction levels.Materials and Methods:This cross-sectional survey adapted from previously used survey tools and validated in our patient group included questions on demographics, communication skills, hospital environment, and the patients’ overall eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
2
11
2
1
Order By: Relevance
“…This result is also consistent with previously performed studies in various medical fields [58,64,65].…”
Section: Patient Satisfactionsupporting
confidence: 95%
See 1 more Smart Citation
“…This result is also consistent with previously performed studies in various medical fields [58,64,65].…”
Section: Patient Satisfactionsupporting
confidence: 95%
“…Older patients tended to be more satisfied than younger patients. In contrast to our results, previous research also found significant gender differences [55][56][57][58].…”
Section: Patient Satisfactioncontrasting
confidence: 86%
“…Patients rated their communication with nurses as slightly better than their communication with doctors (Binsalih et al . ). In a survey of patients upon discharge, effective communication was identified as a factor in their satisfaction (McCaffrey et al .…”
Section: Related Studiesmentioning
confidence: 97%
“…The country has committed vast resources to improving medical care for its citizens, and it earned 26th place according to ranking of the world's health care systems [12]". Additionally, Patients satisfaction is reflected in a good simulator to criticize the quality of health services and can predict both of compliance and application of accreditation standards.…”
Section: Significant Of the Problemmentioning
confidence: 99%
“…It was implemented in tertiary hospital revealed that the patients rated of communication between patients and nurses was slightly better than their communication with physicians [12]".…”
Section: Introductionmentioning
confidence: 99%